Exploring broilers and native fowls of Andaman and Nicobar Islands as a source of β-lactamase-producing Enterobacteriaceae even with limited anthropogenic activities and docking-based identification of catalytic domains in novel β-lactamase variants - Bhowmick, Sneha; Pal, Surajit; Sunder, Jai; Sujatha, T.; De, Arun Kumar; Mondal, Tousif; Singh, Abhishek D.; Joardar, Siddhartha Narayan; Batabyal, Kunal; Dutta, Tapan Kumar; Bandyopadhyay, Samiran; Tiwari, Ananda; et al. (Frontiers in Veterinary Science, 2023)
Objectives The present study was conducted to detect the occurrence of β-lactamase and biofilm-producing Escherichia coli, Salmonella, and Klebsiella in broilers and native fowl reared in the Andaman and Nicobar Islands, India. The study also included molecular docking experiments to confirm the nature of the catalytic domains found in the β-lactamase variants obtained and to reveal the clonal relationship of the isolates with human clinical strains from the database. Materials and methods A total of 199 cloacal swabs were collected from five poultry breeds/varieties (broiler, Vanraja, Desi, Nicobari, and layer) in three districts of the Andaman and Nicobar Islands. E. coli, Salmonella enterica, and Klebsiella pneumoniae were isolated by standard techniques and confirmed by PCR. Phenotypical β-lactamase producers were identified by a double-disc test. The genes (blaCTX, blaSHV, blaTEM, and blaAmpC) were screened, and selected sequences of β-lactamase variants were submitted to DDBJ. Homology modeling, model validation, and active site identification of different β-lactamase variants were done by the SWISS-MODEL. Molecular docking was performed to identify the catalytic domains of the β-lactamase variants. The selected β-lactamase sequences were compared with the Indian ESBL sequences from human clinical strains in NCBI-GenBank. Results In total, 425 Enterobacteriaceae strains were isolated from the collected samples. Klebsiella pneumoniae (42.58%) was found to be the most prevalent, followed by Salmonella enterica (30.82%) and E. coli (26.58%). The phenotypical antibiogram of all 425 isolates showed the highest resistance against oxytetracycline (61–76%) and the lowest against gentamicin (15–20%). Phenotypical production of β-lactamase enzymes was observed in 141 (33.38%) isolates. The isolation rate of β-lactamase producing E. coli, Salmonella enterica, and Klebsiella pneumoniae was significantly higher (p < 0.05) in the birds reared in the South Andaman district (25.6, 17.5, and 18.7%, respectively) than in Nicobar (11.5, 7.6, 7.1%, respectively). Genotyping of the β-lactamase-producing isolates revealed the maximum possession of blaTEM, followed by blaSHV and blaCTX − M. The nucleotide sequences were found to be similar with blaCTX − M−15, blaSHV − 11, blaSHV − 27, blaSHV − 228, blaTEM − 1, and blaAmpC in BLAST search. Distribution of studied biofilm-associated genes in Enterobacteriaceae strains from different varieties of the birds revealed that the layer birds had the maximum possession, followed by Vanraja, Desi, broilers, and Nicobari fowls. The phylogenetic analysis of selected sequences revealed a partial clonal relationship with human clinical strains of the Indian subcontinent. Molecular docking depicted the Gibbs free energy release for 10 different macromolecules (proteins) and ligand (antibiotic) complexes, ranging from −8.1 (SHV-27 + cefotaxime) to −7 (TEM-1 + cefotaxime) kcal/mol. Conclusion and relevance The study revealed β-lactamase variants circulating in the fowl population of the Andaman and Nicobar Islands (India), even in remote places with low anthropogenic activity. Most of the strains possessed blaTEM − 1, followed by blaCTX − M−15. Possession of blaSHV − 11, blaSHV − 27, and blaSHV − 228 in poultry Enterobacteriaceae strains was not reported earlier from any part of the world. The phylogenetic analysis revealed a partial clonal relationship of β-lactamase sequences with the human clinical strains isolated from the Indian subcontinent.